ARBOREAL POETICS IN HOWARD NEMEROVâ€™S â€œTHE THOUGHT OF TREESâ€ AND LUIS H. FRANCIAâ€™S â€œLESSONS OF A TREEâ€ - Yulianto, Henrikus Joko (Sanata Dharma University, 2020)
This paper discusses arboreal poetics in two contemporary poems â€œThe Thought of Treesâ€ by Howard Nemerov, an American poet and â€œLessons of a Treeâ€ by Luis H. Francia, a Filipino one. The objectives of this research are first to identify how Nemerov and Franciaâ€™s vegetal poetics conveys ecological views; second, how their vegetal poetics evokes oneâ€™s ecological awareness to conserve biodiversity and to consume material goods sufficiently. These behaviors help to reduce the exacerbation of climate change phenomenon. This research used qualitative methods, in which the data were words and taken from the two poems and from several sources on trees, climate change, ecopoetry as a kind of criticism belonging to environmental humanities. The result shows that both poems anthropomorphize trees as indispensably interconnected and coexistent with any life forms and the physical environment. This further impacts on humanâ€™s growing ecological conscience not to objectify but to conserve vegetation in particular and other natural resources in general through his sufficient consumption of the material goods for oneâ€™s living necessities.